ANALISA PERFORMANCE THRESER DI PABRIK KELAPA SAWIT (PKS) PTPN V SEI GARO DENGAN METODE OVERALL EQUIPMENT EFFECTIVINESS (OEE) DAN 5S - Mahyunis, Mahyunis; Effendi, Zulham; Tinambunan, Levi Rentiana (Jurnal Agro Fabrica, 2023)
This study aims to analyze things that support the performance of thresher in palm oil mills, determine thresher performance with Overall Equipment Effectiveness (OEE) and 5S methods in palm oil mills and analyze and provide solutions to improve thresher performance with a Total Productive Maintenance approach using the Overall Equipment Effectiveness (OEE) method and 5S on thresher in palm oil mills.. This research was conducted with descriptive and qualitative methods in improving the production performance of threser machines to determine the problems of threser machines that cause a decrease in machine productivity by analysis and discussion. Based on the results of the analysis and description of OEE measurement results in the PTPN V Sei Garo Threser machine, Measurement of the level of machine effectiveness using the Overall Equipment Effectiveness (OEE) method at PTPN V Sei Garo obtained the largest percentage of OEE on the Thresher machine at 91.66% and the lowest at 878.79%. The factors that have the largest percentage of six big losses on thresher machines are Idling and Minor Stoppage Losses of 1% and Equipment Faillure Losses of 0.37%.